Potential role of physical labor and cultural views of menstruation in high incidence of pelvic organ prolapse in Nepalese women: a comparative study across the menstrual cycle - Biswokarma, Yvonne; Brandon, Karen; Lohman, Everett; Stafford, Ryan; Daher, Noha; Petrofsky, Jerold; Thapa, Uma; Berk, Lee; Hitchcock, Robert; Hodges, Paul W. (Frontiers in Medicine, 2024)
Abstract: Introduction: Pelvic organ prolapse (POP) is a significant health concern for young Nepali women, with potential risk factors including pelvic floor trauma from vaginal delivery and heavy lifting. The prevalence of symptomatic POP (SPOP) among nulliparous women in Nepal is 6%, while the general population of Nepali women aged 15-49 years reports a prevalence of 7%. Surprisingly, the average age of SPOP onset in Nepal is 27 years, challenging the assumption that postmenopausal age and vaginal delivery are the sole risk factors. This study aims to investigate the influence of increased intra-abdominal pressure (IAP) during lifting tasks on pelvic organ descent in Nepali women across different menstrual cycle stages. Methods: The study included twenty-two asymptomatic Nepali women aged 18-30 years who regularly engage in heavy lifting. Intra-abdominal pressure was measured intra-vaginally during typical and simulated lifting tasks, which encompassed various scenarios such as ballistic lifting, ramped lifting, and pre-contraction of pelvic floor muscles, as well as coughing, Valsalva maneuver, and pelvic floor contractions. Pelvic floor displacement was recorded using transperineal ultrasound during menstruation, ovulation, and the mid-luteal phase. Results: Results indicated that pelvic floor displacement was greater during menstruation than ovulation when performing a simulated ballistic lifting task (6.0 ± 1.6 mm vs. 5.1 ± 1.5 mm, p = 0.03, d = 0.6). However, there was no significant difference in pelvic floor displacement during lifting when the pelvic muscles were pre-contracted. Conclusion: These findings suggest that lifting heavy loads during menstruation may increase the risk of stretching and injuring pelvic floor supportive tissues, potentially contributing to SPOP in young Nepali women. Pre-contracting pelvic floor muscles during lifting tasks may offer a protective effect. Understanding these factors could aid in developing targeted preventive measures and raising awareness about the impact of heavy lifting on pelvic floor health among Nepali women. Keywords: prolapse, nulliparous, pelvic floor, lifting, menstrual cycle, laxity, compliance, elasticity, stiffness, Chhaupadi